Combinatorics of coxeter groups - Bjorner Anders; Brenti Francesco (New York Springer-Verlag, 2005)
This book is a carefully written exposition of Coxeter groups, an area of mathematics which appears in algebra, geometry, and combinatorics. In this book, the combinatorics of Coxeter groups has mainly to do with reduced expressions, partial order of gro
Keywords: Combinatorics; Coxeter groups